VCT Model Based on Local Wisdom Values in Pancasila and Citizenship Education to Strengthen Students' Social Awareness - Sakman Sakman; Aim Abdulkarim; Kokomo Komalasari; Iim Sitti Masyitoh (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to determine the effectiveness of using the VCT Model based on local wisdom values in Pancasila and Citizenship education to increase students' social awareness. Method: This research used a quasi-experiment with a one-class group pretest-posttest design. This research was conducted at JHS 26 Makassar, Indonesia, with a sample of 31 students. Effectiveness is measured based on the results of the n-Gain test developed by Hake. Results: The research results found that the use of the VCT model based on local wisdom values was practical and effective in increasing students' social awareness as evidenced by the results of the N gain pretest and post-test, which were in the high category with a g- ave of 0.89 and the results of the practical test of the value-based VCT model local wisdom by teachers 92.30% (efficient) and observers 90.98% (very practical). Novelty: This research contributes to preserving cultural heritage as the nation's wealth.